SUPPORTING AND INHIBITING FACTORS IN DEVELOPING GASTRONOMIC POTENTIAL AS A TOURIST ATTRACTION IN SUKOREJO TOURISM VILLAGE, SRAGEN REGENCY, CENTRAL JAVA - Hastuti Nurhayati; Anissa Cahyani (International Journal of Social Science, 2024)
This research aims to determine the supporting and inhibiting factors in developing the potential of gastronomy as a tourist attraction in the Sukorejo Tourism Village. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation. The research informants consisted of managers and culinary activists in the village. The research results show that the supporting factors in developing the potential of gastronomy as a tourist attraction are destination readiness, carrying capacity, cultural attractions, agro-tourism attractions, while low public awareness about the potential and benefits of tourism, skills in processing derivative products can hinder the development of gastronomic potential and tourist attractions in addition to There are also budget limitations which can hinder the realization of tourism projects, most recently the lack of communication and community involvement creates synchronization between destination development and support from the village government. This research concludes that an emphasis on natural, culinary, cultural, agrotourism and accommodation attractions, coupled with support and expectations from the community, is the key to realizing the development of this village's gastronomic potential as an attractive and sustainable tourist destination